Exploring Family Dynamics and Spiritual Well-being Through the Lens of Family Systems Theory - Korun, A. Berke; Satici, Seydi Ahmet (SPRINGER, 2025)
Families play a fundamental role in an individual's emotional development and overall psychological well-being. Grounded in Family Systems Theory, this study investigates the relationship between family boundaries and spiritual well-being, specifically examining the mediating roles of family adaptability, belongingness, and cohesion. Using structural equation modeling, data from 847 participants (M = 24.25, SD = 4.96) were analyzed. Results indicated that family adaptability, belongingness, and cohesion fully mediated the association between family boundaries and spiritual well-being. No direct effect of family boundaries on spiritual well-being was found. These findings contribute to family systems theory by demonstrating that spiritual well-being is shaped not by isolated family processes but through the collective functioning of adaptability, belongingess and cohesion.
Keywords: Family boundaries; Family adaptability; Family belongingness; Family cohesion; Spiritual well-being; MENTAL-HEALTH; COHESION; STRESS; COHERENCE; BEHAVIOR; PARENTS; SENSE; Psychiatry